Organizational change in service stations: implications of energy reform (Revista de Investigaciones Universidad del Quindío, 2020)
Objective: To analyze the process of adaptation to the new business model, permit competition implemented by the Energy Reform in two gas station companies, for the recognition of their capacity to change, risks and their resistance to it. Method: A qualitative study was developed with a phenomenological design to discover how the adjustment to the change of model has been. Results: In the continuing staff training, it has been possible to carry out a correct combination of the work done and the service provided to the users. Limitations: These results are limited by not having the experiences of other companies that decided not to participate in the study. Originality: Provides a vision of change from the actors' experience of a market vision. Conclusions: Energy Reform gave way to companies' opportunity for competition, which led to the search for change initiatives that favor each of them.
Keywords: Organizational change; Energy Reform; New Business Model; Villahermosa; Tabasco